An Analysis of the Advanced Method Corporation (AMCO) approach to Phonics Instruction in First Grade EFL Education at Santo Domingo De Guzman School. - Flores Rengifo, Domenika Gabriela (2024)
This paper analyzed the Advanced Methods Corporation (AMCO) textbook for EFL and phonics instruction among first-grade students. AMCO is an English program for bilingual education that emphasizes communicative teaching principles and the natural acquisition of the English language. The main objective of this research was to examine the AMCO approach to phonics and early literacy that first-grade students at Santo Domingo De Guzmán School need for second grade. To obtain the results, this research adopted a mixed methods design focused on the following tools: structured interviews with elementary English teachers, adapted phonics awareness tests, and unstructured classroom observation. Our analysis has shown that the AMCO textbook does not have the necessary phonics material that first-graders need to cover before advancing to second grade. Through this paper, we conclude that there is a need for complementary materials to strengthen phonics instruction at first-grade levels.